Comparative Effects of Fentanyl, Medazolam, Lignocaine and Propranolol on Controlling the Hemodynamic Pressor Response during Laryngoscopy and Intubation - May S. Al-Sabbagh (College of Pharmacy University of Baghdad, 2017)
Laryngoscopy and tracheal intubation are considered the most invasive stimuli in anesthesia. They provoked cardiovascular responses that include hypertension, tachycardia and dysrhythmias. Various pharmacological approaches have been used to blunt or attenuate such pressor responses. The present study was designed to evaluate the effect of medazolom, lignocaine and propranolol as a valuable adjuvant to fentanyl in attenuating hemodynamic responses to endotracheal intubation in normotensive patients. Thirty two patient with physical status I or II according to the score of American Society of Anesthesiologist (ASA), scheduled for elective surgery under standard general anesthesia, were randomly allocated into four groups (8 patients in each group), assigned as F, M, L and P groups. Each patient in the four groups received 1 Âµg/kg i.v fentanyl. Patients in groups M, L and P are treated with 0.2 mg/kg i.v medazolam, 1.5mg/kg i.v lignocaine and 0.01mg/kg i.v propranolol respectively. Induction of anesthesia was then accomplished with 2mg/kg thiopental sodium followed by1.5mg/kg succinylcholine. Tracheal intubation was performed 2 minutes after induction of anesthesia. Heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure and rate pressure product were measured before induction, after induction and at 2, 4, 6 and 8 minutes after intubation. The results indicated no significant variation in the hemodynamic pressor response in all four groups with tracheal intubation. In conclusion, a minimum effective dose of i.v pre-medications (fentanyl, medazolom, lignocaine and propranolol) were found to be individually successful in attenuating and providing a reliable control of all hemodynamic response changes accompanied the process of laryngoscopy and intubation. Therefore, all are proved effective premedication and no one being superior. Key words:  fentanyl, medazolom, lignocaine, propranolol, endotracheal intubation, hemodynamic response